PROFILE OF DISRUPTION IN THE LANDSCAPE OF THE INDONESIAN BANKING INDUSTRY - Sarwo Edi, Yohanes (Scientia Integritas Utama, 2022)
Disruptions that occur in the business world can penetrate into any business sector and industry, including banking, which is known as an industry that has strict regulations and is not easy for newcomers to enter. This study aims to understand the process of disruption in the banking sector, construct the phenomenon of disruption that occurs, find potential opportunities and risks of threats faced by incumbents in the Indonesian banking industry, and answer the question whether incumbents should be worried about the disruption that occurs. The main data collection technique used is in-depth observation of the phenomenon of disruption that occurs by conducting direct and indirect interviews, group discussion forums (FGD) and documentation studies or even a combination of the three (triangulation). Industrial business landscape analysis techniques use the 4C-Diamonds analysis tool and Industrial Business Model Environmental Analysis with a Business Model Generation approach. The results of the research conducted show that the era of disruption in the Indonesian banking industry sector has been clearly visible since 2016, which was triggered by advances in information technology, especially the internet, high-speed microprocessors, smart devices and the rapid development of fintech. The emergence of the Covid-19 pandemic forced banks to accelerate the adoption of technology and digitization in their financial transaction services and other banking services, to match the changing preferences of customers who prefer to do activities through digital channels. Fintech developments and shifts in customer preferences have also been a trigger for the presence of new players or new entrants, including: fintech companies, technology giants, digital banks and neobanks. Incumbents don't have to worry about any disruptions that may occur, if only they are able to meet the requirements for sustainable growth and are able to adapt to -or even create- environmental scenarios for future business models to come.